2017
DOI: 10.21276/ijlssr.2017.3.1.18
|View full text |Cite
|
Sign up to set email alerts
|

Associations of Obesity Indices with Cardiorespiratory Fitness in Bengali School Going Boys in India

Abstract: ABSTRACT-This study determined the relationship between obesity parameters (Body Mass Index, Waist Hip Ratio, Waist Thigh Ratio and Body Fat Percentage) and cardio respiratory fitness in terms of physical fitness index (PFI) and also were compared the selected physiological parameters (resting pulse rate, respiratory rate and blood pressure) among three body weight categories of selected boys. The present study was carried out in 233 healthy school going Bengali boys aged 11 to <13 years from India. On the bas… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
3
0

Year Published

2017
2017
2020
2020

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(4 citation statements)
references
References 15 publications
1
3
0
Order By: Relevance
“…Jawahar Lal Nehru Memorial Medical College, Raipur, Chhattisgarh, India by Panda et al [18] in the year 2017 and it was concluded that there is a rising burden of hypertension among study population and waist hip ratio was strongly associated with hypertension. From the various studies conducted in the direction [19][20][21][22][23] results seem to be compatible with the outcome of our study, though smaller sample size and lake of gender wise data, have been the major limitations of our study.…”
Section: Discussionsupporting
confidence: 87%
“…Jawahar Lal Nehru Memorial Medical College, Raipur, Chhattisgarh, India by Panda et al [18] in the year 2017 and it was concluded that there is a rising burden of hypertension among study population and waist hip ratio was strongly associated with hypertension. From the various studies conducted in the direction [19][20][21][22][23] results seem to be compatible with the outcome of our study, though smaller sample size and lake of gender wise data, have been the major limitations of our study.…”
Section: Discussionsupporting
confidence: 87%
“…[4] Increased central obesity is reported to lower physical fitness index and cardiovascular efficiency, especially during exercise, due to lower utilization of oxygen per unit of body mass. [5] Obesity in general is associated with increased risk of metabolic syndrome and cardiovascular disease. [6] Many endocrine, inflammatory, neural, and cell-intrinsic pathways get dysregulated in obesity, which independently and in interdependent ways leads to insulin resistance.…”
Section: Access This Article Online Quick Response Codementioning
confidence: 99%
“…Resting heart rate, respiratory rate and blood pressure were higher in overweight and obese children compared to normal children; indicates a lower level of cardiovascular efficiency in overweight and obese boys compared to normal weight boys. [14] Antioxidant/pro-oxidant imbalance in hypertension can lead to detrimental consequences and long term adverse effects like atherosclerosis and cardiovascular disease. More extensive study is required to check the association between hypertension and oxidative stress.…”
Section: Research Articlementioning
confidence: 99%